EVEKTIFITAS MODEL BRAINSTORMING DALAM MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS PADA MATERI KEHIDUPAN MANUSIA PRAAKSARA - Siti Lusiana; Lili Dianah; Sudarmi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the effectiveness of the brainstorming model in improving students’ critical thinking skills on the topic “Human Life in the Prehistoric Era” in grade X at SMA Plus Al Qomariyah. The background of this research is based on the low level of students’ critical thinking skills, which is caused by the dominance of conventional teaching methods that lack encouragement for analytical, evaluative, and reflective activities. The research employed Classroom Action Research (CAR), conducted in two cycles consisting of the stages of planning, action, observation, and reflection. The research subjects were 35 students who were divided into heterogeneous groups to carry out brainstorming activities, namely proposing ideas freely, selecting, and evaluating ideas based on logic. Data were collected through a critical thinking test measuring the indicators of interpretation, analysis, evaluation, and inference, as well as student and teacher activity observation sheets. The results show a significant improvement from the pre-cycle, with an average score of 62.5 and a mastery level of 30%, to 73.5 and 65% in cycle I, and finally to 83.6 and 88% in cycle II, exceeding the minimum mastery criteria (KKM). These findings prove that the implementation of brainstorming can address students’ weaknesses in drawing conclusions and evaluating information logically. Thus, the brainstorming model is proven to be effective in improving critical thinking skills in learning, and it is recommended to be applied consistently with an emphasis on idea evaluation so that students’ critical thinking skills can develop optimally